Emergent economies, divergent paths : economic organization and international trade in South Korea and Taiwan - Feenstra, Robert C. (Structural analysis in the social sciences, 2006)
The economies of South Korea and Taiwan in the second half of the 20th century are to scholars of economic development what the economy of Britain in the late 18th and early 19th century is to economic historians. This book offers an original explanation of these development paths.